Demonstrating Value, Improving Education and Doing Right by Patients: The Role of Patient-Reported Outcomes in Student-Run Free Clinics and Recommendations for Implementation - Trevor Staples; Anndee Neuman; Anne Thackeray (Journal of Student-Run Clinics, 2022)
Emphasis has been placed on patient-reported outcomes as a means to improve quality in healthcare. Likewise, patient-reported outcomes have the potential to benefit student-run free clinics in several important ways. Unfortunately, student-run free clinics infrequently incorporate patient-reported outcomes into the care process. This perspective article highlights the need for routine collection of patient-reported outcomes in student run free clinics and recommends resources and future directions to promote widespread use of patient-reported outcomes in student-run free clinics.